Angiotensin-Converting Enzyme (ACE) genetic variation and longevity in Peruvian older people: a cross-sectional study - Teodoro J. Oscanoa; Edwin C. Cieza; Frank A. Lizaraso-Soto; María L. Guevara; Ricardo M. Fujita; Román Romero-Ortuño (Taylor & Francis Group, 2020)
Background: Some studies have suggested that the insertion(I)/deletion(D) polymorphism of the Angiotensin-Converting Enzyme (ACE) gene may be associated with human longevity, especially in centenarians. However, this association is still controversial. Besides, there have been no studies in Peruvians. Aim: To describe the age distribution of the ACE polymorphism in a convenience sample of Peruvian older people. Subjects and methods: This was a cross-sectional study in 104 Geriatric Day Hospital patients in Lima, Perú. The ACE polymorphism was determined in all patients. For the purpose of association with age, the sample was divided into four categories: young (< 65), youngest-old (65-74), middle-old (75-84) and oldest-old (85 or more). Results: The distribution of genotype frequencies was consistent with a population in Hardy-Weinberg equilibrium (p = 0.62). The number (%) of D/D, I/D and I/I genotypes in the young was 2 (14.3%), 3 (21.4%) and 9 (64.3%), respectively; in youngest-old: 4 (11.4%), 15 (42.9%) and 16 (45.7%); in middle-old: 6 (12.2%), 20 (40.8%) and 23 (46.9%); and in oldest-old: 0 (0.0%), 4 (66.7%) and 2 (33.3%). A chi-square analysis showed no significant differences in genotype distribution between age groups (p = 0.647). Conclusion: No significant age differences were found in the distribution of the ACE polymorphism in this sample. Further studies with greater statistical power are recommended.